Inequality and historical legacies: evidence from post-communist regions. Issue 6 (2nd November 2019) - Libman, Alexander; Obydenkova, Anastassia
ABSTRACT: Egalitarianism is one of the key elements of the communist ideology, yet some of the former communist countries are among the most unequal in the world in terms of income distribution. How does the communist legacy affect income inequality in the long run? The goal of this article is to investigate this question by looking at a sample of sub-national regions of Russia. To be able to single out the mechanisms of the communist legacy effects more carefully, we look at a particular aspect of the communist legacy – the legacy of the Communist Party of the Soviet Union (CPSU). We demonstrate that the sub-national regions of Russia, which had higher CPSU membership rates in the past, are characterised by lower income inequality. This, however, appears to be unrelated to the governmental redistribution policies; we link lower inequality to the prevalence of informal networks.